HEART BIRTH DEFECTS: DIAGNOSTIC AND THERAPEUTIC EXPERIENCE IN UZBEKISTAN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article explores the diagnostic and therapeutic approaches to heart birth defects in Uzbekistan. It highlights the advancements, challenges, and outcomes observed in the clinical management of congenital heart defects (CHDs). By analyzing national health data and specific case studies, the paper identifies key trends and proposes strategies to improve early detection and treatment outcomes.